THE INFLUENCE OF RUNNING DICTATION METHOD ON STUDENTS’ DESCRIPTIVE TEXT WRITING ABILITY - Ela Nurmala (Jurnal Bahasa Inggris Terapan, 2020)
This research was intended to find out whether or not there was a significant influence of running dictation on students’ descriptive text writing ability and to find out students’ responses toward running dictation method used for improving students in writing descriptive text. The research methodology was a quasi-experimental design. The population of this research was the tenth-grade students during the first semester of SMA Negeri 1 Jalan Cagak. The data from pre-test and post-test were analyzed by using SPSS 22.00. The data from questionnaires were analyzed by using a Likert Scale. The computation results of Independent Sample t-test it was obtained that Sig = 0.006 and α = 0.05. It means Ha is accepted because Sig < α = 0.05. It can be concluded there is a significant influence of running dictation method on students’ descriptive text writing ability. Furthermore, the results of questionnaires showed that most of the students (80%) gave positive responses toward running dictation method in writing descriptive text. It can be put forward that Running Dictation is effectively used for teaching writing descriptive text, the students are motivated, enjoyable to learn and their interest through English learning especially writing is rising.